ANALYZING FACTORS THAT DRIVE THE CUSTOMER PREFERENCE IN USING CREDIT CARD. CASE STUDY OF BANKS IN MANADO - Dinar, Devid E. (Sam Ratulangi University, 2016)
The banking sector has flourish in Indonesia with a hopeful prospect. Banks and other financial organization are in massive competition to provide better service to their customer. The breakthrough was made by the banking sector is credit card. Credit card is a plastic card mostly known as plastic money that bears an account number assigned to a cardholder with a credit limit used to purchased goods and pay for service. A credit card increases purchasing power, eases the transaction process, allows for obtaining credit facility available. This research is design to identify the factors that drive the customer preference in using credit card. The type of this research confirmatory research. The method used to analyze the data is the confirmatory analysis factor. There are 20 items in this research that determine for questionnaire and to find the factors. The result of this research found there are 5 items that had no high correlation with other items. Those there five items was not valid, because the value of 5 items below 0.5. This research findings 5 factors from 15 variables, those are: discount, promotion, reputation, service quality, convenience service, low interest rate, media awareness, cash advance, customer service, security, communicating information, responsiveness, accessibility, purchase protection, insurance. Â